An analysis of the library usage patterns of comparative literature students at the College of Arts and Letters, University of the Philippines Diliman - Tolentino, Chiara Rica T.; Dela Torre, Nathalie N. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2007)
This study sought to analyze and assess the library usage patterns of comparative literature students of the University of the Philippines College of Arts & Letters and their relationship to specific personal and environment factors. The personal factors included age, gender, year level, student status and the distance of residence from campus. Environment factors considered are the faculty influence and the library services, facilities, and resources. Particularly, this study sought to determine how the comparative literature students evaluate the library's services, facilities, and resources specifically if: (1) the users are aware of the UP College of Arts and Letters Library collection; (2) the condition of the library's services, facilities, and resources, as evaluated by the comparative literature students, have a significant relationship with their library usage pattern; and (3) determine the problems encountered by the comparative literature students when using the UP College of Arts and Letters Library. Finally, the study sought to offer recommendations and suggestions for the improvement of the UP College of Arts and Letters Library.
The main respondents of this study are the comparative literature students who were currently enrolled during the 1st semester Academic Year 2007 - 2008. The entire population who are currently enrolled were distributed survey questionnaires as a data-gathering tool. The data gathered from the respondents were collated and analyzed using the Statistical Package for the Social Sciences (SPSS), using frequency and percentage distributions and the Pearson correlation to test the hypothesis.
The study found a significant relationship between the student's library usage patterns and influence of the faculty members. The same positive result was found of the students' research needs. Some recommendations for the improvement on the library's resources, facilities, and services are offered in this paper based on the comments and suggestions of the respondents and the researcher's observation.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Diliman. College of Arts and Letters -- Students; University of the Philippines Diliman, College of Arts and Letters Library -- Use studies; College students in literature